2019
DOI: 10.1556/2006.8.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

Are sports bettors looking at responsible gambling messages? An eye-tracking study on wagering advertisements

Abstract: Background and aims The broadcast of wagering advertisements during televised sports matches has been associated with various adverse outcomes. In order to counter these effects, legislative bodies require wagering operators to include responsible gambling messages in their advertisements; however, the effectiveness of these messages is unclear. This study sought to examine the extent to which responsible gambling messages are looked at, in the wider context of gambling advertisements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
(57 reference statements)
2
34
0
Order By: Relevance
“…In their current form, such messages have been highlighted for their likely inadequacy in reducing gambling-related harm. For example, a recent eye-tracking study of bettors and non-bettors demonstrated that very few visual fixations are placed on these messages in comparison to other wagering information displayed within sports betting advertisements [ 60 ]. Moreover, when specific RG messages are in fact actively perceived by bettors, the messages may fail in terms of their supposed purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In their current form, such messages have been highlighted for their likely inadequacy in reducing gambling-related harm. For example, a recent eye-tracking study of bettors and non-bettors demonstrated that very few visual fixations are placed on these messages in comparison to other wagering information displayed within sports betting advertisements [ 60 ]. Moreover, when specific RG messages are in fact actively perceived by bettors, the messages may fail in terms of their supposed purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom (UK), Ipsos MORI (2019) reported that the amount of money spent on gambling advertising had increased from £264,657,325 in 2015 to £328,945,916 in 2018 (a 24% increase) across various media platforms, particularly for lotteries and bookmakers. Given the popularity of sports betting, as well as the large audiences attracted to live sporting events, the broadcast of wagering advertisements appears to have become widespread, especially during televised sporting events (Columb et al 2020;Hing et al 2015;Lole et al 2019;Lopez-Gonzalez et al 2017;Purves et al 2020). For example, during the 2018 FIFA (soccer) World Cup, betting advertisements were the most prevalent type of advertisements shown, totaling almost 90 min of screen time during the tournament (Duncan et al 2018).…”
mentioning
confidence: 99%
“…Research into the type of wagering inducement promotion has found some inducement types to be more popular than others, for example, for sports bettors often favor the "risk-free" or reduced risk inducement (Hing et al, 2014a(Hing et al, , 2017(Hing et al, , 2019Lole et al 2019). Other research has reported that both treatment-seeking sports bettors and general population sports bettors were encouraged to spend more due to advertising, particularly in response to free bet and deposit offers (Hing et al 2015).…”
mentioning
confidence: 99%
“…Some warning labels are extremely generic (e.g., in Australia, 'Gamble responsibly'; in the UK, 'When the fun stops, stop'; or in Ontario, 'Play smart'). These labels provide little information to meaningfully guide consumers (Newall et al, 2019c) and might be ignored due to sheer repetition of content (Lole et al, 2019). Other gambling warning labels warn gamblers only about the product they are currently using, an approach that has been most consistently applied to electronic gambling machines (Wohl et al, 2014;Ginley et al, 2017;McGivern et al, 2019).…”
Section: Introductionmentioning
confidence: 99%